Penerapan Model Pembelajaran Kooperatif Tipe Team Games Tournament (TGT) Berbantuan Media Permainan Monopoli Dalam Meningkatkan Hasil Belajar Peserta Didik Pada Mata Pelajaran Ekonomi - Agustin, Riska Alawiyah; Nurdianti, Raden Roro Suci; Sadiah, Ati (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
The main problem related to this research is the low learning outcomes of students in economic subjects. This study aims to determine the increase in student learning outcomes before and after treatment as well as differences in the improvement of student learning outcomes in experimental classes with a team games tournament (TGT) type cooperative learning model assisted by monopoly game media and control classes with a jigsaw learning model. The research was conducted at MAN 3 Tasikmalaya. The research method used was quasi-experimental method. The research design used was nonequivalent pretest-posttest control group design. The population in this study was class XI MAN 3 Tasikmalaya Academic Year 2024/2025 totaling 143 students. The sample used was XI-J which amounted to 36 people as an experimental class and XI-K class which amounted to 36 people as a control class with sampling using purposive sampling technique with a total of 72 students. The instrument used was a multiple choice question in economics as many as 25 questions. The data analysis technique uses the help of the SPSS 25 program, namely the paired sample t-test and the independent sample t-test with a significance level of 0.000. So it can be concluded that there is an effect of the team games tournament (TGT) learning model assisted by monopoly game media in improving the learning outcomes of students in the economic subject of labor material in the experimental class, there is an effect of the jigsaw learning model in improving the learning outcomes of students in the economic subject of labor material in the control class, and the average posttest value of the experimental class is higher than the control class.